A proteomics and metabolomics analysis of the mechanism of lipid accumulation in yeast - Shi, Jiahua (2015)
Energy shortage and environmental concerns have become urgent problems all over the world. Microbial production of high-energy fuels represents one of the viable options for sustainable energy supply due to its considerable advantages, such as being renewable, biodegradable and nontoxic. Oleaginous yeast strains are capable of accumulating lipid with a yield of more than 20% in their cells. Accumulation of intracellular lipid in oleaginous yeast cells has been studied for providing an alternative supply for energy, biofuel. Numerous studies have been conducted on increasing lipid content in oleaginous yeasts. However, few explore the mechanism of the high lipid accumulation ability of oleaginous yeast strains. A comprehensive understanding and exploration of lipid accumulation mechanism in oleaginous yeast remains insufficient. Using iTRAQ-coupled two-dimensional liquid chromatography mass spectrometry (2D LC-MS/MS) analysis and gas chromatography-mass spectrometry, we report here a time course comparative study of protein profile and metabolite profile of oleaginous yeast strains. The development of proteomics and metabolomics platforms will greatly facilitate understanding of lipid accumulation mechanisms in oleaginous yeast. Two oleaginous yeast strains and one non-oleaginous yeast strain were selected as our investigated subjects. Rhodosporidium toruloides and Cryptococcus albidus are reported oleaginous yeast strains, producing up to 65.2% and 46.3% lipid of their cell dry weight, respectively. Non-oleaginous yeast Saccharomyces cerevisiae, whose lipid content is merely less than 15%, is selected as a control for comparison. Each strain was cultured in optimized medium and collected at early, middle and late lipid accumulation stages. Two dimensional LC-MS/MS approach has been applied for protein profiling together with isobaric tag for relative and absolute quantitation (iTRAQ) labelling method. 132 proteins were identified when three yeast strains were all at early lipid accumulation stage; 122 and 116 proteins were found respectively within cells of three strains collected at middle and late lipid accumulation stages. Significant up-regulation or down-regulation synthesis of proteins was observed among yeast strains. Essential proteins correlated to lipid synthesis and regulation were detected. For example, the up-regulated proteins, ADP, ATP carrier protein 2 (AAC2p), ATP synthase subunit beta, mitochondrial (ATP2p), are closely relevant with the energy production and transportation, providing steady supplement of energy of lipid synthesis. To complement our proteomics analysis, the metabolomics analysis was carried out to establish the changes in metabolites which are truly reflective of the physiological state of cells. The intracellular metabolites of cells during different lipid accumulation phases were compared using gas chromatography-mass spectrometry. Fifteen metabolites exhibited marked differences along with lipid accumulation in S. cerevisiae. Thirteen metabolites displayed different expression levels in C. albidus along lipid content change from 10.73% to 27.74% of its cell dry weight. 10 metabolites were identified to have remarkable changes for R. toruloides when lipid content accumulated from 14% to 45%. When time-course based comparison among the three strains was carried out, 10, 14 and 9 differentially expressed metabolites were found in the cells at early, middle and late lipid accumulating stages, respectively. Significant changes in metabolite levels correlated to lipid synthesis were identified, such as lysine, succinate and citrate. Our results highlight the potential of using proteomics and metabolomics platforms to study lipid accumulation mechanisms in oleaginous yeast. Comparison within cells between non-oleaginous yeast and oleaginous yeast strains demonstrates characteristic proteomic and metabolic signatures. Taken together, these findings demonstrate the feasibility of using LC-MS-based proteomics and GC-MS-based metabolomics platforms to understand lipid accumulation mechanisms. It is to be hoped the platforms developed in this study can also be applied to the investigation of other microorganisms and would contribute to further genetic engineering for higher lipid accumulation in yeast.